Marriage Premium and Class - Roberto Bonilla; Francis Z. Kiraly; John Wildman (Center for Economic Studies and ifo Institute (CESifo), 2017)
We present an equilibrium model with inter-linked labour and marriage markets, and argue that search frictions play an important role in explaining the male marriage premium. If men are viewed as bread-winners within households, this expectation aects their job search behaviour, which in turn can lead to marital wage gaps ranked across productivities. Male heterogeneity is neither necessary nor sufficient for this premium. Nonetheless, when coupled with female heterogeneity in the marriage market, male reservation wages linked to productivities do affect the resulting assortative matching structure, and equilibrium marriage classes exhibit their own patterns of marital wage differentials. Using UK data on wages, male/female heterogeneity and marital classes, we also carry out the first empirical test of the role of search frictions in generating the male marriage premium.
Keywords: D83; J12; J64; 330; frictional labour markets; frictional marriage markets; marriage premium; classes